IMPLEMENTASI KEBIJAKAN SELEKSI TERBUKA DALAM JABATAN PIMPINAN TINGGI PRATAMA DI KOTA PEKANBARU PROVINSI RIAU - A. Mius; Ermaya Suradinata; Muh. Ilham; H. M. Aries Djaenuri (Fakultas Politik Pemerintahan IPDN, 2019)
Implementation of Open Selection Policy in Primary High Leadership Position in Pekanbaru City, Riau Province. The Open Selection Policy in the Top Manager is the implementation of Law Number 5 Year 2014 concerning the State Civil Apparatus (SCA). The objective of open selection is to create apparatuses that have professionalism based on merit system. Implementation of the Open Selection Policy in the City of Pekanbaru is the first policy implemented in Sumatra. This study uses a descriptive design with a qualitative approach. Data was collected by interviewing informants consisting of regional heads, heads of selection teams, SCA who passed selection, observation and documentation, then analyzed to get a description. The results of the study indicate that the Implementation of the Open Selection Policy for TOP Managers in the City of Pekanbaru is carried out with the effectiveness of communication and clear distribution authority for each organ implementing the policy. Large funds are needed to build assessment centers, suit workloads and program incentives. There are indications of time uncertainty at each selection stage. The ideal model for open selection policy in Pekanbaru City should be an enrichment of the Edwards III Policy Implementation policy which is equipped with environmental variables and transparency indicators in communication variables. Keywords: policy, open selection, management, merit system.